Development of a Patient-Reported Outcome Measure (PROM) for Dysgeusia During Treatment With Smoothened (SMO) Inhibitors for Basal Cell Carcinomas: The SMO-iD Questionnaire - Elisa Camela; Alessia Villani; Sonia Sofia Ocampo Garza; Claudia Costa; Gabriella Fabbrocini; Matteo Megna; Luca Potestio; Angelo Ruggiero; Massimiliano Scalvenzi (Mattioli1885, 2023)
Introduction: Dysgeusia may occur during conventional or target-therapies and affect patients adherence-to-treatment. Therefore, it should be monitored to improve clinical outcome. To date, available questionnaires on dysgeusia relate to traditional antineoplastics and do not apply to target-therapies as the pathogenetic mechanism and clinical expression differ. Objectives: To develop a patient-reported outcome measure (PROM) to screen for and monitor the occurrence and severity of dysgeusia in patients under Smoothened (SMO) inhibitors: the SMO-iD questionnaire. Methods: Patients with locally advanced basal cell carcinomas referring dysgeusia under SMO inhibitors at the University Hospital of Naples Federico II, were enrolled between January-December 2020. The PROM was elaborated based on chemotherapy-induced dysgeusia (CiTas) scale (development phase) and then validated by measuring internal consistency and reliability (validation phase). Results: Thirty-nine patients were enrolled and interviewed every 8 weeks. In the first phase, 160 CiTas questionnaires were collected, and the SMO-iD questionnaire was developed. In the second phase, 195 SMO-iD questionnaires were recorded, and reliability and validity assessed. Cronbach alpha was 0.89. Conclusions: The SMO-iD questionnaire is a validated questionnaire that shows high face and content validity as well as high internal consistency and reliability. Hence, it may be introduced in daily clinical setting to monitor dysgeusia in patients under SMO-inhibitors.